Factors Influencing Finansial Distress With Liquidity As A Moderating Variabel - Fitri Apriyana; Tri Kunawangsih Purnamaningrum; Pardomuan Sihombing (International Journal of Economics Accounting and Management, 2025)
The aim of this research was to test and analyxe the impact of profitability, capital structure also activity ratio regarding financial distress with liquidity as a moderating variabel in infrastructure companies. This study uses infrastructure sector firms registered on the Indonesia Stock Exchange (IDX) during the periode 2019 – 2023. Purposive sampling was the method employed for sampling, so that the sample obtained amounted to 19 an the total observations used were 95 observations. The data analysis method employed is Moderated Regression Analysis (MRA) using Eviews 12 application. The outcomes of this research concluded that profitability demonstrates a positive and a considerable influence on financial distress, capital structure have a negative and significant effect on financial distress, activity also liquidity ratios do not have a considerable effect on financial distress. Liquidity can moderate a relationship between capital structure on financial distress, but liquidity cannot moderate the relationship between profitability and activity ratio on financial distress